The Effect of CRHBP rs10062367 Polymorphism and Parenting Styles on Internalizing Problems in Preschoolers: The Moderating Effect of Sensory Processing Sensitivity - Zeng, Siyao; Liu, Cuizhen; Wang, Zhenhong (Child psychiatry and human development, 2024)
The present study aimed to examine how CRHBP rs10062367 polymorphism interacted with parenting styles and sensory processing sensitivity (SPS) to impact on preschoolers’ internalizing problems. A total of 446 preschoolers ( M age = 4.55, SD = 1.07) participated in the study and their saliva were extracted to genotype the CRHBP rs10062367 polymorphism, and their parents were invited to complete a battery of questionnaires to assess parenting styles, preschoolers’ SPS, and internalizing problems. Results indicated that high SPS preschoolers with A allele exhibited fewer internalizing problems under the condition of positive parenting while they exhibited more internalizing problems under the condition of negative parenting. The findings provide support for the Differential Susceptibility Model/Biological Sensitivity to Context Theory that A allele of rs10062367 and high SPS might be the “susceptibility markers” of children to environments.